2022
DOI: 10.3390/diagnostics12071746
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Serum Pepsinogens with and without Co-Testing with Gastrin-17 in Gastric Cancer Risk Assessment—Results from the GISTAR Pilot Study

Abstract: Introduction––Serum pepsinogen tests for gastric cancer screening have been debated for decades. We assessed the performance of two pepsinogen assays with or without gastrin-17 for the detection of different precancerous lesions alone or as a composite endpoint in a Latvian cohort. Methods––Within the intervention arm of the GISTAR population-based study, participants with abnormal pepsinogen values by ELISA or latex-agglutination tests, or abnormal gastrin-17 by ELISA and a subset of subjects with all normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…36 The biomarkers serum PgI and II levels, the PgI/II ratio, serum gastrin-17 and H. pylori serology have long been measured and explored, alone or in combination, to detect advanced or late-stage atrophic gastritis. [253][254][255] Low serum PgI and a low PgI/II ratio can provide a non-invasive diagnosis of advanced stage atrophic gastritis, and, importantly when H. pylori serology is also negative, endoscopy is recommended by the MAPS II Guideline Update 2019. 42 An observational study evaluating screening tests in 28 Japanese patients with confirmed histological AIG reported a 78.6% positive predictive value with a serum gastrin >172 pg/mL, or with cut-off values of PgI and PgI/II ratio 14.5 ng/dL and 2.1, respectively.…”
Section: Commentmentioning
confidence: 99%
“…36 The biomarkers serum PgI and II levels, the PgI/II ratio, serum gastrin-17 and H. pylori serology have long been measured and explored, alone or in combination, to detect advanced or late-stage atrophic gastritis. [253][254][255] Low serum PgI and a low PgI/II ratio can provide a non-invasive diagnosis of advanced stage atrophic gastritis, and, importantly when H. pylori serology is also negative, endoscopy is recommended by the MAPS II Guideline Update 2019. 42 An observational study evaluating screening tests in 28 Japanese patients with confirmed histological AIG reported a 78.6% positive predictive value with a serum gastrin >172 pg/mL, or with cut-off values of PgI and PgI/II ratio 14.5 ng/dL and 2.1, respectively.…”
Section: Commentmentioning
confidence: 99%
“…By estimating the verification probability, PS demonstrates a clear and direct relationship with the verification problem, in this case, the PVB problem. Recent implementations of PVB correction methods can be seen in studies evaluating MRI and ultrasound in prostate cancer [ 15 ], serum pepsinogens in gastric cancer [ 16 ], and fine needle aspiration cytology in breast cancer [ 17 ], where the studies utilized BG-based and MI methods.…”
Section: Introductionmentioning
confidence: 99%